Health Literacy and Antibiotic Use Behavior Among Working Age People in Muak Lek District, Saraburi Province - Makornkan, Supatcharee; Jarujit, Saengdao (Human Behavior, Development and Society, 2024)
This cross-sectional study investigated the levels of health literacy, antibiotic use behavior, and their relationships among working age people in Muak Lek Sub-district, Muak Lek District, Saraburi Province. The research instrument was a self-administered health literacy and antibiotic use behavior questionnaire that was completed by 352 respondents. Cronbach’s alpha coefficient test produced reliability scores for these two question groups of .98 and .92 respectively. Data were analyzed using descriptive statistics and Pearson's correlation coefficient. The study’s results revealed widespread usage of antibiotics by working age people, most of whom had moderate levels of health literacy. Health literacy was positively, but weakly, related to proper antibiotic use behavior at the .001 level of statistical significance (r = .268, p < .001). Working age people with low levels of health literacy were found to misuse antibiotics; however, rational use of such medications is important since incorrect use of drugs may have negative effects on health. This study provides data about antibiotic usage patterns to support public health professionals and relevant agencies in developing future preventive strategies.